University Museums as Library Partners in Transformation of Inclusive and Interdisciplinary Institution - Pungki Purnomo; Azwar, Muhammad; Ida Farida; Amir Fadhilah; Lili Sudria Wenny (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2026)
Background: In the landscape of Indonesian Islamic Higher Education, the museums at UIN Ar-Raniry Banda Aceh and UIN Maulana Malik Ibrahim Malang serve as pioneering institutional models. These repositories function as "learning laboratories," utilizing Object-Based Learning (OBL) to bridge the gap between historical artifacts and contemporary academic discourse. Purpose: This study investigates the perceptions of museum managers and academics regarding the dual role of university museums: as internal pedagogical supports for campus life and as external instruments for community engagement and cultural diplomacy. Methods: Adopting a qualitative comparative approach, data were gathered through in-depth interviews and direct field observations at both university sites. The analysis focused on the integration of museum resources into the "Tri Dharma" (Teaching, Research, and Community Service) framework of Indonesian higher education. Findings: The study shows that these museums are very important for the intellectual lives of students and faculty and are also very important for reaching out to the community. However, despite their success in fostering cultural engagement, their potential is often hampered by a lack of formal institutional recognition and integrated management protocols. Originality/Value: This research underscores the necessity for a robust legal and policy framework, facilitated by university leadership and the Ministry of Education, to formalize the status of university museums. Strengthening these institutional foundations is essential for the sustainable development of museum-based pedagogy within Indonesia’s State Islamic Universities.